Population Health Management: Is There Any Role for Orthopaedics?. (3rd May 2017) - Boden, Scott D.; Smith, Brian T.; Handley, Matthew
Abstract : Abstract: The next phase of health-care reform will accelerate the formation of integrated delivery systems and the creation of value and savings through population health management. Accomplishing this goal requires 3 key factors, including (1) enabling groups of physicians and hospitals to legally work together to cover a broad geographic area, (2) the formation of integrated delivery systems that cover the low to high-acuity and post-acute care spectrums, and (3) identifying mechanisms through which a subspecialty can impact the health of a population of patients. At first glance, it would be easy to assume that this is largely a primary care initiative and that orthopaedic surgeons cannot influence population health since they often just repair things after they have broken or worn out. This symposium will challenge that assumption and demonstrate the potential for orthopaedic surgeons to play a major role in population health management. Some of the mechanisms include implementing shared decision-making for elective procedures, reducing premature/unnecessary imaging and subspecialty referrals, improving bone health (osteoporosis prevention and fall risk assessment), and developing payment methodologies to reward population-based, rather than individual-based, positive musculoskeletal outcomes.